Statewide prioritization of vernal pools for pond-breeding amphibians in New Jersey. (1st August 2023) - Craft, Hannah E.; Fouad, Geoffrey; Sterrett, Sean C.
Abstract: Vernal pools are required habitat of pond-breeding amphibians, yet their legal protections in the United States are not established, leaving vernal pools vulnerable to development and habitat fragmentation. Seasonally, amphibians migrate to breed in vernal pools. Roads and upland forest loss can jeopardize that migration, resulting in mortality. Vernal pools surrounded by fewer roads and more upland forest are of greater preservation priority in the management of amphibian populations. This study presents a statewide preservation prioritization of New Jersey's 13, 594 vernal pools mapped in a previous work. The prioritization builds on that work by calculating a preservation score based on a combination of six characteristics regarding habitat fragmentation in the migratory area surrounding a vernal pool. The scores are calculated at a range of migration distances to account for a variety of amphibian species, and it is found that the different distances make little difference to preservation scores because of the overall small scale at which amphibians migrate. Results are presented that show clear parts of the state that should be prioritized for vernal pool preservation, mainly in areas where fewer roads lead to less development and habitat fragmentation. Areas of preservation priority are further refined using geographic clusters which show assemblages of vernal pools with favorable migratory areas. A special class of vernal pools has migratory areas that are uninterrupted by roads. These vernal pools and the assemblages of favorable migratory areas are often in preserved lands, but those that are not should receive special attention in both the field confirmation of amphibian habitat and subsequent protective measures, which can vary from conservation easements to citizen science interventions in sustaining local amphibian populations. Furthermore, surrounding states that also have a significant amount of vernal pools may be able to use this prioritization framework for preservation and conservation. Highlights: A preservation prioritization of 13, 594 vernal pools in New Jersey is presented. Preservation scores based on habitat fragmentation at different migration distances. Scores vary little at different migration distances of pond-breeding amphibians. Areas of preservation priority for pond-breeding amphibians are clearly shown. Management decisions may be guided by mapped vernal pool assemblages.